Original paperType A behavior in individuals with psoriasis as a determinant of acceptance of illness - Basińska, Małgorzata A.; Drozdowska, Marta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction: Type A behavior (TAB) pattern is a complex of behavioral characteristics or a life style expressing excessive vigilance, aggressiveness, excitability, inclination to compete and a feeling of time pressure and excessive responsibility. It is known to be a risk parameter of somatic illnesses and affects the course of disease. Aim : To qualify the relation between TAB and acceptance of illness (AI) in a group of individuals with psoriasis. Material and methods : The sample included 60 patients with psoriasis. Patients were subjected to three testing methods: Framingham Type A Behavior Pattern Measure, Acceptance of Illness Scale and a personal survey. Results: The results show differences in the intensity of a typical subcomponent of TAB pattern, time urgency, between healthy women and diseased men and between women and men in the diseased group of people. Women, in comparison to men, are predisposed to time urgency regardless of their health condition. The clinical state of diseased people does not differentiate the level of TAB. In the group of women with psoriasis there is a negative correlation between a tendency to follow the TAB pattern and its subcomponent time urgency and AI. Diseased women with a lower AI have a higher predisposition to functioning according to TAB. Type A is related to functioning in the state of illness by AI. Conclusions : Type A behavior plays the role of a risk predictor in the investigated group, but its role as a risk predictor of psoriasis requires further research.